Ethical Artificial Intelligence in Libraries : Transforming Information Services, User Trust, and Knowledge Access (International Journal of Scientific Research in Science and Technology, 2026)
The fast adoption of Artificial Intelligence (AI) into library systems is changing the nature of information services, shifting the nature of user interactions, and altering the concept of knowledge access. Starting with the intelligent search and recommendation systems up to automated cataloging and virtual reference service, AI presents massive possibilities in improving efficiency, personalization, and inclusivity in libraries. Nevertheless, these developments also pose significant ethical issues associated with data privacy, biased algorithms, transparency, responsibility, and maintaining intellectual freedom which are the fundamental values of librarianship. In this paper, the ethical aspects of AI use in libraries are considered, and the discussion of the ethical concerns of responsible and human-oriented AI practices is conducted to build trust among the users and provide fair and transparent access to information. It addresses the concepts of ethics, policy-making, and the changing role of librarians in the mediation of AI-based services. Posing fairness, explainability, and respect of user rights, the study identifies strategies of harmonizing AI technologies with library ethics and professional standards. Finally, the implementation of AI ethically is put forth as the key to the continued existence of libraries as social organizations that uphold democratic access to knowledge in the digital era.